JQUERY SEBAGAI KOMPONEN USABILITAS ANTARMUKA APLIKASI WEB - Muhammad Aris Ganiardi; Irma Salamah; RD. Kusumanto (Jurnal Poli-Teknologi, 2015)
Abstract Web applications are most widely used by the user in the cooperative information portal. This web application type is used as a communication tool to distribute information to the general public relating to the the organization or company. State Polytechnic Sriwijaya develop information portal that is used to distribute information related to academic activities in the form of announcements and news that happens in the State Polytechnic Sriwijaya. Portal of information held by the State Polytechnic Sriwijaya has not implemented the quality factor of reusability in Web application development cycle. The purpose of this research is to implement JQuery as the application of the quality factor of reusability at the Polytechnic of Sriwijaya information portal. JQuery is applied on the portal interface to allow users to use the information portal. Results obtained from this study that more information portal interesting and attractive. Keywords : JQuery, Usabilitas, Aplikasi Web Abstrak Aplikasi web yang paling banyak digunakan oleh pengguna kooperasi berbentuk portal informasi. Jenis aplikasi web ini digunakan sebagai alat komunikasi untuk mendistribusikan informasi ke masyarakat umum berkaitan dengan organisasi atau perusahaan. Politeknik Negeri Sriwijaya mengembangkan portal informasi yang digunakan untuk mendistribusikan informasi berkaitan dengan kegiatan akademik berbentuk pengumuman dan berita yang terjadi di Politeknik Negeri Sriwijaya. Portal informasi yang dimiliki oleh Politeknik Negeri Sriwijaya belum menerapkan factor kualitas usabilitas dalam siklus pengembangan aplikasi web. Tujuan penelitian ini adalah mengimplementasikan JQuery sebagai penerapan factor kualitas usabilitas pada portal informasi Politeknik Negeri Sriwijaya. JQuery diterapkan pada antarmuka portal untuk memudahkan pengguna menggunakan portal informasi tersebut. Hasil yang didapatkan dari penelitian ini portal informasi yang lebih menarik dan atraktif. Kata kunci : JQuery, Usability, Web Application